A new type of bladeless turbine for compressed gas energy storage system - Wang, Qin; Zhu, Zhengyang; Chen, Wei; Zhou, Yang (Frontiers in Chemistry, 2022)
Nowadays, energy storage engineering is an important means to relieve the problem of energy shortage. In this investigation, we designed a kind of vaneless turbine originating from Tesla turbine with the diameter and the air gap of 250 mm and 0.5 mm, respectively. Importantly, such vaneless turbine removes the feature of air outlet in the middle and adopts other ways of entering and leaving on both sides, so as to strengthen the rotor, because there is no need for a large hole in the middle of the rotor. Furthermore, the rotor dynamics characteristics of the vaneless turbine is calculated by six modes at different. We also obtained the critical speed in different modes. Besides, the flow field performances, such as the velocity and pressure of fluid (air), are investigated using finite element simulation method. In addition, the bench test was built to obtain the output characteristics of vaneless turbine. The maximum output torque is about 5.56 N·m at 992 rpm, and the maximum rotational speed of the vaneless turbine reaches 3200 rpm. Our work can provide new ideas and guidance for the design and research of the new generation of vaneless turbine.